2018
DOI: 10.3389/fpsyt.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Malingering: A New Tool to Identify Made-Up Depression

Abstract: Major depression is a high-prevalence mental disease with major socio-economic impact, for both the direct and the indirect costs. Major depression symptoms can be faked or exaggerated in order to obtain economic compensation from insurance companies. Critically, depression is potentially easily malingered, as the symptoms that characterize this psychiatric disorder are not difficult to emulate. Although some tools to assess malingering of psychiatric conditions are already available, they are principally base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
(48 reference statements)
1
32
0
1
Order By: Relevance
“…During the experimental task, the MouseTracker software 25 automatically recorded a number of features relating to the response of the mouse in spatial and temporal terms. Mouse parameters that the literature reported to be the most sensitive to deception detection were collected 5,33,35,47 . Specifically, the following features were captured for each mouse trajectory: The idealized trajectory represented the virtual straight line connecting the starting point to the endpoint (the response label).…”
Section: Materials Underreporting Validity Scales (L K S) Of the Mmentioning
confidence: 99%
See 1 more Smart Citation
“…During the experimental task, the MouseTracker software 25 automatically recorded a number of features relating to the response of the mouse in spatial and temporal terms. Mouse parameters that the literature reported to be the most sensitive to deception detection were collected 5,33,35,47 . Specifically, the following features were captured for each mouse trajectory: The idealized trajectory represented the virtual straight line connecting the starting point to the endpoint (the response label).…”
Section: Materials Underreporting Validity Scales (L K S) Of the Mmentioning
confidence: 99%
“…In the present study, mouse dynamics were used for the first time to investigate faking-good behaviour with respect to the validity scales of two personality questionnaires (the MMPI-2 and PPI-R). In the literature, mouse dynamics have been shown to provide useful behavioural cues to identify deception 33,64 , and the technique has already been successfully applied to detect faking-bad respondents 5,47 . In the present research, only for the L scale the results were consistent with the findings reported in previous studies, which have shown that, compared to honest participants, fakers take more time to respond to stimuli 18 and outline wider trajectories when selecting a response 5 , albeit with small observed effects.…”
Section: Differences In Mouse Movements and Trajectories Between Honementioning
confidence: 99%
“…Second, focus on the precision of item estimates, it is inherently more difficult to recover true item parameters for ideal point models with the normal probability density function model, if comparing with that for dominance models which derive item estimates with the normal ogive model (Brown and Maydeu-Olivares, 2010). Considering GGUM's mathematical complexity for estimation difficulties, some studies related to detect faking used other methods, for example, techniques based on reaction times, and scored invalidity scales (Sellbom and Bagby, 2010;Monaro et al, 2018;Roma et al, 2018;Mazza et al, 2019), generally obtained superior accurate outcomes. Finally, practically speaking, the use of ideal point models seems not to result in any improvement for predictive validity, if comparing with dominance models (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many methodologies and techniques have been developed for detecting response distortion over the years, for example, machine learning models, reaction times, regression analysis, etc. (Dunn et al, 1972;Sellbom and Bagby, 2010;Jiménez Gómez et al, 2013;Monaro et al, 2018;Roma et al, 2018;Mazza et al, 2019). Still, there is a concern about the perceptions and interpretations of the change on items due to intentional dissimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to validate the mouse dynamics as a tool to detect deception using an alternative technique to unexpected questions to induce cognitive load in liars. Particularly, here we propose the use of complex sentences (Monaro et al, 2018b;Monaro et al, 2018c), which exceed the mentioned above limit of the unexpected questions.…”
Section: Introductionmentioning
confidence: 99%